Adolescent Life Stress and the Cortisol Awakening Response: The Moderating Roles of Attachment and Sex. (1st February 2016) - Miller, Kelly F.; Margolin, Gayla; Shapiro, Lauren Spies; Timmons, Adela C.
Abstract : This longitudinal study investigated how past versus current life stresses relate to adolescents' cortisol awakening response (CAR), an index of hypothalamic–pituitary–adrenal activity. Ninety‐nine adolescents reported previous year life stress at ages 12 and 18. At the second assessment, participants also provided self‐reports of parent and peer attachment and 3 days of cortisol samples. Current stress was associated with heightened CAR for both males and females, whereas past stress was associated with attenuated CAR for males. Attachment to peers buffered the relationship between past stress and attenuated CAR for all adolescents; attachment to parents was a buffer for male adolescents only. Results demonstrate the protective roles of adolescent relationships and highlight sex differences in biopsychosocial development across adolescence.